Role of endoscopic duodenojejunal bypass liner in obesity management and glycemic control - Willian Ferreira Igi; Victor Lira de Oliveira; Ayah Matar; Diogo Turiani Hourneaux de Moura (Korean Society of Gastrointestinal Endoscopy, 2024)
The treatment of obesity and its comorbidities ranges from clinical management involving lifestyle changes and medications to bariatric and metabolic surgery. Various endoscopic bariatric and metabolic therapies recently emerged to address an important therapeutic gap by offering a less invasive alternative to surgery that is more effective than conservative therapies. This article comprehensively reviews the technical aspects, mechanism of action, outcomes, and future perspectives of one of the most promising endoscopic bariatric and metabolic therapies, named duodenojejunal bypass liner. The duodenojejunal bypass liner mimics the mechanism of Roux-en-Y gastric bypass by preventing food contact with the duodenum and proximal jejunum, thereby initiating a series of hormonal changes that lead to delayed gastric emptying and malabsorptive effects. These physiological changes result in significant weight loss and improved metabolic control, leading to better glycemic levels, preventing dyslipidemia and non-alcoholic fatty liver disease, and mitigating cardiovascular risk. However, concern exists regarding the safety profile of this device due to the reported high rates of severe adverse events, particularly liver abscesses. Ongoing technical changes aiming to reduce adverse events are being evaluated in clinical trials and may provide more reliable data to support its routine use in clinical practice.